2023
DOI: 10.4174/astr.2023.104.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course in children with equivocal appendicitis on computed tomography: a retrospective cohort study

Abstract: Purpose Appendectomy is one of the most common surgeries in children. Although various radiological examinations are performed, they do not always reveal a definitive diagnosis of appendicitis. This study aimed to investigate the clinical course of equivocal appendicitis, identify the factors associated with appendectomy, and suggest appropriate management for these patients. Methods Patients younger than 19 years who visited Seoul National University Bundang Hospital w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Appendicitis accounts for more than 50% of emergency procedures in the field of surgery [ 1 2 ]. In particular, surgery for appendicitis is considered the gold standard in cases with features such as a large diameter of the appendix, appendicolith, periappendiceal infiltration, and rupture [ 3 4 5 ]. However, recent studies have reported that successful treatment can be achieved with conservative management in the case of early-stage appendicitis without these advanced features [ 6 7 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Appendicitis accounts for more than 50% of emergency procedures in the field of surgery [ 1 2 ]. In particular, surgery for appendicitis is considered the gold standard in cases with features such as a large diameter of the appendix, appendicolith, periappendiceal infiltration, and rupture [ 3 4 5 ]. However, recent studies have reported that successful treatment can be achieved with conservative management in the case of early-stage appendicitis without these advanced features [ 6 7 8 ].…”
Section: Introductionmentioning
confidence: 99%